Toxic Masculinity Beliefs and Impulsivity in Men: Moderating Role of Gender Role Beliefs - Gilani, Misha; Bashir, Shamshad (ACADEMIA International Journal for Social Sciences, 2025)
The aim of the current research was to test the impact of the beliefs of toxic masculinity on impulsivity in men and to test how gender role beliefs moderate the effect of beliefs of toxic masculinity in the sociocultural environment in Pakistan. Masculine norms and values in patriarchal cultures are usually conducive to emotional repression, dominance and toughness of behaviour, which in turn might lead to inefficient emotional regulation and disruptive behavioural consequences. The quantitative cross-sectional research design was applied, and 220 adult men were sampled using convenience sampling and having various educational and occupational backgrounds. Standardized psychological measures were used to test toxic masculinity beliefs, impulsivity and gender role beliefs. The correlation and moderation analysis were used to analyze the data in order to determine predictive relationships and interaction effects. The results showed that there is a strong positive correlation between the toxic masculinity beliefs and impulsiveness, which implies that the higher the beliefs in the inflexible masculine norms, the more impulsive tendencies. Moreover, gender role beliefs also played a significant role in stepping this relationship, with guys that had stronger beliefs about gender roles demonstrating a more significant association between toxic masculinity and impulsivity, and guys with less entrenched beliefs demonstrated weaker associations. These results indicate that gender norms which are internalized are critical in controlling behavior and psychological functioning in men. The research has real-world implications on clinical psychology, counseling, and psychoeducational interventions in that the authors touch on the challenge of deregulated gender role beliefs to decrease impulsive behavior and encourage a more healthful emotional expression. This work is culturally grounded in its analysis of toxic masculinity and impulsivity in Pakistani men.